Intersex Between Sex And Gender In Cause Et Cure. (2nd October 2021) - Charmaille, François·e
ABSTRACT: This article argues that intersex is present in medieval medical texts outside of the medieval concept of hermaphroditism. The phlegmatic man, the phlegmatic woman, and the sanguine man, in the twelfth-century medical text Cause et cure, all exhibit intersex characteristics. The close examination of the terms in which these figures are described also shows that the elaboration of intersex in this text directly challenges the modern distinction between sex and gender. Contrary to Joan Cadden's influential analysis of Cause et cure, I argue that the text has a robust nonbinary system of sexual difference. In particular, phlegm is consistently characterised as an intersex category. The examination of phlegm's intersex properties leads to a re-examination of viriditas [greenness]. This study reveals that viriditas acts as a masculine and masculinising substance, in an almost hormonal sense. Its imbalanced presence in phlegmatic bodies causes them to diverge from prelapsarian ideals of sexual dimorphism. Cause et cure identifies the Fall as the cause of humoral imbalance, and illness. The text precisely describes atypical sex as one of the effects of this fallen state. I identify this through an intersex reading which contests the sex/gender distinction and the reification of sex.